Anticipatory thinking vs Fiqh Tawaqqu': integrating the Western and Islamic perspectives - Abu Hassan, Muhammad Ikram; Kamarulzaman, Wirawani (Asian Scholar Network, 2023)
With an emphasis on the notion of Fiqh Tawaqqu', this article examines anticipatory thinking from both Islamic and Western vantage points. Anticipatory thinking is an essential cognitive skill for both individuals and teams, as it entails the capacity to proactively foresee forthcoming obstacles and possibilities. This paper examines the components of anticipatory thinking within the Western culture, encompassing forecasting, scenario planning, risk evaluation, opportunity identification, and adaptability. It emphasises the advantages of anticipatory thinking, including enhanced decision-making capabilities, readiness, and flexibility in response to changes. On the contrary, the article explores the Islamic viewpoint through an elucidation of Fiqh Tawaqqu' and an analysis of its importance within the realm of Islamic law (fiqh). Fiqh Tawaqqu' pertains to the anticipation of action results through the application of experience and evidence, with an emphasis on maslahah (benefits) for the ummah (community) and the prevention of damage (mafasid). The paper examines the acceptance and rejection of Fiqh Tawaqqu' among Muslim scholars, addressing the objections raised by some early Islamic figures. Furthermore, the paper offers examples of Fiqh Tawaqqu' that were initially met with skepticism but have proven to be relevant in contemporary contexts. It emphasizes the role of Fiqh Tawaqqu' in the development of jurisprudence and fatwa, enabling scholars to provide solutions to emerging societal issues. Finally, the paper explores the integration of anticipatory thinking and Fiqh Tawaqqu', highlighting the commonalities and potential synergies between these two approaches. It underscores the importance of forward-thinking and strategic planning in both Western and Islamic contexts to address complex challenges and shape a better future. This study presents a comprehensive overview of anticipatory thinking and Fiqh Tawaqqu', developing a deeper awareness of their significance and ramifications in today's environment.